Log-domain all-pass based multiphase sinusoidal oscillator - Prommee, Pipat; Somdunyakanok, Montri (My University, 2012)
This paper describes the design of a current-mode multiphase sinusoidal oscillator (MSO) based on log-domain all-pass network. The first order all-pass filter circuit is realized by first order all-pass filter. In each block of all-pass filter includes ten bipolar transistors and a grounded capacitor. The simulation of three-phase sinusoidal signal generator is carried out by SPICE. The 2.5V power supply is used for achieving the frequency from 700Hz - 70MHz by adjusting the bias currents. For bias currents 100 μA, the frequency of the signal is obtained around 7MHz and total harmonic distortion is measured around 1.5%. The three signal outputs of the proposed MSO are equally spaced in phase and amplitude. © 2012 IEEE.
Keywords: All-pass Filter; Electronically-controlled; High-frequency; Log-domain; Low-voltage; Multiphase Sinusoidal Oscillator